Cancer chemopreventive and chemotherapeutic activities of flavonoid-positive fractions from Annona squamosa Linn. leaf extracts - Brady, Gladys Asuncion P. (Punzalan) (Institute of Biology, College of Science, University of the Philippines Diliman, 2008)
This study aimed to find out the characteristic types and chromatographic profile of compounds contained in flavonoid-positive fractions in leaf extracts of Annona squamosa Linn. using standard phytochemical isolation and purification methods. The fractions obtained at every step of the purification process were screened initially for the first anticancer assay to test for free radical scavenging ability using DPPH assay. A final isolate was obtained, characterized through physical and spectral data, and turned out to be a benzylisoquinoline nitrogenous compound structurally related to flavonoids. This final isolate from Annona squamosa leaves has moderate antioxidant property as demonstrated by its ability to scavenge the free radical DPPH with an IC50 of 86.3ug/ml. This property was further confirmed when it conferred protection to brine shrimps against potential lethal effect of H2O2. The brine shrimp assay also demonstrated that the isolate is nontoxic. It was however not observed to be an inhibitor of xanthine oxidase. When tested for potential to cause differentiation of promyelocytic HL60 cells, it demonstrated strong activity as inducer towards monocytic differentiation. This suggests additional bioactivities of a characterized compound to add to the chemical constituents studied and reported for members of the plant family Annonaceae.